China's New Soft Power Strategy - O. V. Zinevich; N. V. Selezneva (Vestnik MGIMO-Universiteta)
The article focuses on the Chinese concept and strategy of using soft power to create an attractive image of the country. In the age of fierce competition for global/regional leadership, the concept of soft power has become the mainstream in China's foreign policy and was considered by Chinese politicians and experts as a tool to strengthen the influence through the introduction into the cultural space of other countries, the dissemination of language and cultural codes in order to create a positive image of China. The Western-based concept of soft power in China has been thoroughly analyzed and specified. Supported by a context-based approach, the article shows how, having previously criticized the concept of Joseph Nye, Chinese scientists and experts developed a specifically Chinese theory of soft power of culture (中国文化软实力), which was used in the foreign and domestic policy of the state and served as the basis for the observed changes in the strategy of using soft power. Based on the analysis of Chinese sources, the authors of the article conclude that at the beginning of the XXI century, the buildup of soft power through the creation of a network of Confucius Institutes was presented by China as a policy for mutual gain in the international arena. With the ascendance of Xi Jinping, the soft power of culture as a resource and tool of China's external influence is leaving the frontier of the political agenda. The foreign policy vector of the soft power of culture is redirected inward, and culture, which until recently openly acted as a driver of soft power in foreign policy, moves to the internal track and fits into the concept of "four self-confidences" and "double circulation", focusing on the qualitative component, while maintaining its high foreign policy significance for the Chinese policymakers.